Development of a Formoterol-Loaded PLGA Nanocarrier Targeting Neuroinflammation and Neurodegeneration in an LPS-Induced Rat Model of Parkinson's Disease - Maher, Rebecca (Trinity College Dublin. School of Pharmacy & Pharma. Sciences. Discipline of Pharmacy, 2026)
Therapies for neurodegenerative disorders like Parkinson’s disease are limited in efficacy and tolerability, largely due to poor drug penetration across the BBB and off-target peripheral actions, leading to poor side effect profiles. Polymeric nanoparticles are advantageous for brain drug delivery due to their safety profiles, drug-loading capacity, controlled-release properties and potential for drug repurposing. The intranasal route is also emerging as an attractive strategy for bypassing the periphery to deliver therapeutics to the brain. The aim of this work was to develop a polymeric nanoparticle, using the FDA-approved poly(lactic co-glycolic acid) (PLGA) polymer, as a vehicle for intranasal delivery and repurposing of experimental anti-inflammatory therapy formoterol in a preclinical rat model of PD-related neuroinflammation and degeneration following in vitro validation of biocompatibility, sustained drug release and anti-inflammatory effects in cell culture. Nanoparticles were prepared using a polyethylene glycol (PEG)-PLGA copolymer by nanoprecipitation. PEG-PLGA nanoparticles were analysed for size and surface charge, and their biocompatibility was evaluated in primary rat glial and neuronal cultures. PEG-PLGA were loaded with experimental anti-inflammatory drug formoterol (Form) and further characterised. In vitro drug release from Form-PEG-PLGA and Form-PEG-PLGA embedded in a mucoadhesive and thermosensitive chitosan hydrogel was quantified by high performance liquid chromatography (HPLC) coupled to UV detection. Form-PEG-PLGA (equivalent to 10 μM of drug) was applied to primary glial cultures stimulated by interferon γ (IFNγ; 50 ng/ml) or lipopolysaccharide (LPS; 100 ng/ml) and the expression of inflammation associated genes was assessed. The resulting conditioned media (CM) was transferred to primary rat neurons for assessment of neuronal complexity. Unloaded PEG-PLGA, both alone and when incorporated into a hydrogel, were tested for compatibility with human peripheral blood mononuclear cells (PBMCs). A hydrogel containing the contrast agent manganese (Mn2+) was administered intranasally to rats, and MRI was performed to validate the nose-to-brain route of drug delivery. Form-PEG-PLGA-gel were administered intranasally to adult Wistar rats daily for 7 or 3 days, prior to an intraperitoneal (i.p) LPS challenge (0.25 mg/kg) and brain expression of pro-inflammatory markers was analysed. Finally, rats were administered Form-PEG-PLGA intranasally prior to stereotactic unilateral injection of LPS into the substantia nigra. Motor function was assessed using the cylinder, stepping, rotarod and amphetamine-induced rotations tests. Post-mortem analysis of microglia and dopaminergic cell bodies in the substantia nigra was then performed. 100 nm unloaded and formoterol loaded PEG-PLGA were synthesised. PEG-PLGA were compatible with primary rat glia and neurons as well as human PBMCs in vitro. Form-PEG-PLGA and Form-PEG-PLGA-gel displayed a sustained drug release profile in vitro and the resulting profiles were a good fit to both the Korsmeyer-Peppas and Weibull models of release kinetics. Form-PEG-PLGA reduced the expression of inflammation associated genes v Il1b, Tnfα, Nos2 and Cd40 in stimulated glia compared to control and free formoterol and protected against the loss of neuronal complexity associated with the transfer of CM from IFNγ and LPS treated microglial cultures. Intranasal administration of the Mn2+-gel resulted in brain accumulation of the contrast agent in vivo. Intranasal delivery of Form-PEG-PLGA-gel attenuated LPS induced expression of Il1b, Tnfα, Nos2 and Cd40 in both the cortex and striatum of the rat brain. Form-PEG-PLGA-gel administered intranasally reduced motor impairment, neuroinflammation and dopaminergic cell loss in the LPS rat model of Parkinson’s disease-related neurodegeneration. Together, these results indicate that drug encapsulation within polymeric nanoparticles, combined with intranasal drug delivery, represents a promising strategy for targeted brain drug delivery. Form-PEG-PLGA exhibited potent anti-inflammatory and neuroprotective effects both in vitro and in a preclinical model of inflammation-associated neurodegeneration, highlighting its potential as a therapeutic approach for neurodegenerative disorders such as Parkinson’s disease.
APPROVED
Keywords: poly(lactic co-glycolic acid) (PLGA); intranasal; neuroinflammation; formoterol; Parkinson's disease; nanoparticle